2019
DOI: 10.18203/2319-2003.ijbcp20192644
|View full text |Cite
|
Sign up to set email alerts
|

Study of drug prescription pattern in ischemic heart disease patients

Abstract: Background: Drug utilization pattern studies helps to screen, assess and propose appropriate modifications in prescription practices, this would help to make patient care rational and cost effective. Study was intended to analyse the drug prescribing pattern for treatment of Ischemic heart disease using WHO indicators.Methods: This is a cross sectional observational study conducted on ischemic heart disease patients admitted at inpatient department of medicine in a tertiary care teaching hospital. The study co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
3
0
0
Order By: Relevance
“…So there is almost equal proportion of generic and ethical prescriptions in OPD.Both the groups had a significant reduction in LDL and total cholesterol in our study. Our study results were similar to a study on prescription pattern of drugs in ischemic heart disease by Mahadeo P et al 6 which showed that 1498 (29.99%) drugs were prescribed by with generic names. In study by Nagabushan H et al 7 , drugs prescribed by their generic names were 52.9% which is also similar to present study.…”
Section: Discussionsupporting
confidence: 91%
“…So there is almost equal proportion of generic and ethical prescriptions in OPD.Both the groups had a significant reduction in LDL and total cholesterol in our study. Our study results were similar to a study on prescription pattern of drugs in ischemic heart disease by Mahadeo P et al 6 which showed that 1498 (29.99%) drugs were prescribed by with generic names. In study by Nagabushan H et al 7 , drugs prescribed by their generic names were 52.9% which is also similar to present study.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, it was seen that IHD was most common in elderly patients. This is similar to the results of the study by Sawant MP et al 18 wherein the majority (59.6 %) of the patients were in the age group of 61-80 years and only 4.6 % of patients were from the age group 21-40. This is also similar to the study by Saju et al 19 wherein the majority (47.4 %) of the patients belonged to the age group of 61-79 years and only 5.2 % of patients were from the age group of 21-39 years.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the incidence of IHD was predominant in men (76.3 %). This predominance is similar to the studies by Sawant et al, 18 Panchaksharimath et al 21 and Gaur et al 22 On the contrary, Shankar et al 23 showed that there was a slightly more percentage of woman patients (51.94 %) suffering from IHD. In this study, IHD patients came from different geographical regions of Rajasthan.…”
Section: Discussionsupporting
confidence: 86%